2003
DOI: 10.1073/pnas.1834302100
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's disease-affected brain: Presence of oligomeric Aβ ligands (ADDLs) suggests a molecular basis for reversible memory loss

Abstract: A molecular basis for memory failure in Alzheimer's disease (AD) has been recently hypothesized, in which a significant role is attributed to small, soluble oligomers of amyloid ␤-peptide (A␤). A␤ oligomeric ligands (also known as ADDLs) are known to be potent inhibitors of hippocampal long-term potentiation, which is a paradigm for synaptic plasticity, and have been linked to synapse loss and reversible memory failure in transgenic mouse AD models. If such oligomers were to build up in human brain, their neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

55
834
1
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 997 publications
(900 citation statements)
references
References 51 publications
55
834
1
10
Order By: Relevance
“…The availability of antibodies specific to small soluble aggregates (antibody 6 in Fig. 1) therefore enables the role of such species in protein aggregation diseases to be probed in detail [61,77,78]. Remarkably, the oligomer-specific generic antibodies have been reported to be capable of protecting cultured cells against the toxicity of aggregates derived from a variety of proteins [61].…”
Section: Elucidation Of the Mechanism Of Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of antibodies specific to small soluble aggregates (antibody 6 in Fig. 1) therefore enables the role of such species in protein aggregation diseases to be probed in detail [61,77,78]. Remarkably, the oligomer-specific generic antibodies have been reported to be capable of protecting cultured cells against the toxicity of aggregates derived from a variety of proteins [61].…”
Section: Elucidation Of the Mechanism Of Toxicitymentioning
confidence: 99%
“…By using antibodies specific to small soluble aggregates, the presence of such aggregates has been identified in brain sections from transgenic mice models and from sufferers of Alzheimer's disease [61,77,78]. The ratio of the amount of this type of aggregate in AD-brains versus control brains has been estimated to be up to 70:1 [78].…”
Section: Elucidation Of the Mechanism Of Toxicitymentioning
confidence: 99%
“…Thus, it may be reasonable to speculate that NSAIDs could prevent the development of AD, not only through suppressing chronic neuroinflammation and reducing the amount of soluble Aß(1-42) peptide levels, but also through directly inhibiting the deposition of fAß in the brain. In relation to the latter scenario, it may be essential to evaluate the effect of NSAIDs on the Aß oligomer formation in a future study, because the Aß oligomer has been reported to be the most neurotoxic form of all the Aß aggregates (Gong et al, 2003). Yang et al (2005) recently reported that curcumin prevented Aß42 oligomer formation and toxicity between 0.1 and 1.0 µM, which is consistent with our EC 50 values of curcumin for the anti-amyloidogenic and fibril-destabilizing activity (Ono et al, 2004b).…”
mentioning
confidence: 99%
“…Recent data indicates that neuronal injuries and death have been correlated with the status of Ab-42 (Sponne et al, 2004;Kriem et al, 2005). Despite there are studies suggesting the role of soluble Ab-42 in promoting the growth of neurapophysis and enhancing neuron survival in a short time, other researches has shown that soluble Ab-42 oligomers may be the proximate effectors of AD and that Ab-42 in soluble oligomeric status can induce neuronal death (Gong et al, 2003;Kim et al, 2003;Florent et al, 2006). The neurotoxic molecular mechanisms of soluble Ab-42 oligomers remain unknown.…”
Section: Discussionmentioning
confidence: 99%